Peningkatan Hasil Belajar Matematika Melalui Model Pembelajaran Interaktif di SMP Negeri 1 Samigaluh - Nurhayati, Radenroro Rita (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2022)
Mathematics learning that emphasizes the situation of students' learning requires strategies, approaches, methods and techniques that can make students active in learning. This study aims to determine the improvement of mathematics learning outcomes in statistics material through interactive learning models for class VIII students in the second semester of the 2021/2022 academic year at SMP Negeri 1 Samigaluh. The instruments used in this study were learning management observation sheets, student activity observation sheets, and mathematics learning outcomes tests. The data analysis technique used in this study is the average of the results of observations and tests. The results of this study indicate that: 1) there is an increase in the number of students who achieve complete scores, 2) there is an achievement of student activities during the learning process with good categories, and 3) there is an achievement of teacher learning management with good criteria.